Comparative Study on Two Pretreatment Processes for Chemical Phase Analysis of Gold in Geological Samples by Atomic Absorption Spectrometry. (10th July 2019) - Tang, Xiaodan; Li, Hang; Liu, Hongyan; Li, Bing; Zhao, Yuyan; Lu, Jilong; Zhou, Jian; Liu, Qingqing
Abstract : Sample pretreatment is important for chemical phase analysis of elements. In this study, the geological samples of the Laozuoshan gold mine are chosen to pretreat by ultrasonic centrifugation and cyclotron oscillation, and the content of gold in eight chemical phases (water-soluble, ion exchange and clay adsorption, organic matter bound, iron-manganese oxide bound, naked or seminaked, carbonate bound, sulfide bound, and insoluble silicate states) is determined by atomic absorption spectrometry. The results show that the gold content of water-soluble, ion exchange and clay adsorption, iron-manganese oxide, and naked or seminaked states in the rock and ore samples is low, and some samples have high gold content of insoluble silicate states in the two methods. However, the gold content of organic matter bound, carbonate bound, and sulfide bound states obtained by ultrasonic centrifugation and cyclotron oscillation methods is significantly different. According to the X-ray fluorescence spectrometry data and the actual geological condition, the result given by the cyclotron oscillation method is more reasonable. The gold content of sulfide bound state in sediment samples is the highest and consistent with the mineral information, which could be applied to preliminarily predict the rock and ore conditions in the corresponding mining areas. In contrast with ultrasonic centrifugation, the cyclotron oscillation method has the advantages of simplicity, high efficiency, practicality, and environmental protection, and it can be better used for the determination of gold chemical phase state in geological samples by atomic absorption spectrometry.